Association of premorbid adjustment with symptom profile and quality of life in first episode psychosis in a tertiary hospital in tehran, iran. - Javad Mahmoodi-Gharaei; Anahita Basirnia; Neda Abedi; Behrang Shadloo; Sara Jafari; Niloofar Salesian; Mohsen Djalali; Vandad Sharifi (Iranian Journal of Psychiatry, 2010)
Objective: Poor premorbid adjustment has been reported to be a predictor of more severe psychotic symptoms and poor quality of life in such psychotic disorders  as  schizophrenia.  However,  most  studies  were  performed  on chronic schizophrenic patients, and proposed the likelihood of recall biases and the effect of chronicity.  The aim of this study was to investigate these factors in a sample of first episode psychotic patients, as a part of Roozbeh first episode psychosis project (RooF). Method: Premorbid adjustment was assessed using Premorbid Adjustment Scale (PAS) in 48 patients with the first psychotic episode who were admitted to Roozbeh Psychiatric Hospital. The severity of symptoms was measured using Positive and Negative Scale (PANSS) in three subgroups of positive, negative and general subscales. Quality of life was measured using WHO QOL ,and Global Assessment of Functioning (GAF) was also measured. Results: The mean age was 24 years. Poor Premorbid adjustment in late adolescence  was  significantly  associated with  more  severe  symptoms according  to  PANSS  negative symptoms  (p=0.019,  r=0.44).  Furthermore, sociability  and  peer  relationship  domains  had  a  positive  correlation  with PANSS negative subscale scores (r=0.531, p=0.002 and r=0.385, p=0.03, respectively).  There  were  no  significant  differences  between  males  and females in premorbid adjustment. Furthermore, this study failed to show any differences  between  affective  and  non-affective  psychosis  in  premorbid functioning. Conclusion: Our study confirms poor premorbid adjustment association with more  severe  negative  symptoms  and  poor  quality of  life in  a sample of Iranian first episode psychotic patients.